A challenging diagnosis of rare co-existent multiple myeloma and prostate adenocarcinoma: a systematic review of case reports - Iqbal , Rashid; Rehman, Shafi; Sukaina, Mahnoor; Ullah, Hameed; Hameed, Maha; Chattha, Uzair (Journal of the Pakistan Medical Association, 2023)
Objective: To review biochemical parameters, clinical characteristics, demographics, radiological and histopathological findings, treatment modalities and outcomes used to examine patients with coexisting multiple myeloma and prostate adencocarcinoma. Method: The systematic review comprised search on PubMed, Google Scholar, Science Direct and the Directory of Open Access Journal databases for case reports published till June 1, 2022. The search was done in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines using appropriate key words. Case reports included were those dealing exclusively with human subjects, were published in the English language and had free, full-text, public access. Quality assessment was done using Joanna Briggs Institute's Critical Appraisal Checklist for Case Reports. Data was extracted and the case reports were evaluated for demographic, diagnostic and treatment parameters. Results: Of the 515 studies initially identified, 5(0.97%) were analysed; all males with mean age 68.6 years (SD= 10.78). The most common symptom reported at presentation was low back pain 3(60%), Osteolytic lesions were seen in 4(80%) patients on imaging with elevated prostate surface antigen levels. Anaemia was found in 3(60%) patients and 2(40%) had thrombocytopenia. Conclusion: Multiple myeloma and prostate adenocarcinoma can coexist although it is rare. Awareness regarding the possible coexistence of the two prominent cancer types may further help clinicians during their practice in considering multiple myeloma as a differential diagnosis when encountered with patients having osteolytic bony lesions along with elevated levels of prostate-specific antigen.